Impact of the color of equipment on competition outcomes in Premier League karate - Berglez, J.; Arvidsson, D. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. Research is needed to better understand the color of uniform and its underlying effects in sports, in order to achieve fairness and equal opportunities for athletes. Problem and aim. In studies where the impact of the color of athletes` equipment on the outcome of matches has been investigated, the results have varied. The aim of this study was to investigate if the color of the protective equipment worn by karate kumite athletes had an impact on the competition outcome after excluding seeded athletes. Methods. A total of 351 matches in the 2020 Premier league competition were analyzed. Binomial analysis was used to determine differences in a match outcome by the color of equipment. T-test for independent groups was used to investigate the difference in points scored, recovery time and the number of warnings based on the color of the equipment. Results. The blue equipment worn by karate kumite competitors was associated with a higher proportion of wins (58.5% vs. 41.5%, p = 0.03) and more points scored (383 vs. 290 points, p = 0.01) than the red equipment, only among male athletes. The mean (sd) recovery time was longer for both male (12.0 ± 1.3 vs. 7.1 ± 1.0 min, p = 0.004) and female (11.0 ± 0.9 vs. 6.5 ± 0.7 min, p = 0.001) athletes wearing red rather than blue. However, recovery time was not associated with more wins, for either male (p = 0.63) or for female (p = 0.62) athletes. Conclusions. In conclusion, blue equipment in karate kumite may lead to more wins and more points scored than for male athletes wearing red.